SU-PhysioDB: A physiological signals database for body area network security - Karaoğlan Altop, Duygu; Levi, Albert; Tuzcu, Volkan (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a new physiological signals database, SU-PhysioDB, that contains simultaneous measurements of electrocardiogram (ECG), blood pressure (BP) and body temperature (BT) signals. SU-PhysioDB can be used to evaluate the performance of the security mechanisms designed for the communication among the biosensors within Body Area Networks (BANs). We present a detailed description of our SU-PhysioDB database along with providing a performance comparison of two specific physiological parameter generation techniques using a public database and our SU-PhysioDB da-tabase. Results show that our SU-PhysioDB database is a pros-pering option to be used while evaluating the performance of a bio-cryptographic security infrastructure designed for BANs.
Keywords: Bio-Cryptography; Blood Pressure; Body Area Networks; Body Temperature; Electrocardiogram; Physiological Signals